Filicide: A Case Series Study of eight cases on Medicolegal Profile and Circumstances (Journal of Forensic Medicine & Toxicology, 2025)
Background: Filicide, the murder of a child by a parent is a complex phenomenon. It has various characteristics and causes. Even though rare, the outcome of filicide is more pronounced and long lasting compared to other types of murders. Maternal and paternal filicides are deaths of children when the killer/perpetrator is the mother and father of the victim. Material and Methods: This article presents 8 cases of filicide where the parents killed the children. These cases were studied from the postmortem records during the past five years, i.e., from 2020-2024. Results: Most of the cases were maternal filicides. The age of the victims ranged from newborns to adolescents. Mothers usually prefer soft methods of homicide whereas fathers prefer hard methods of homicide. Conclusion: A better understanding and knowledge of potentially fatal paternal/ familial dynamics, methods espoused for filicide could facilitate the identification of risk and enable effective intervention strategies. This case series highlights pattern of filicides in Kadapa region in order to enlighten the health professionals, clinicians and the general population about the importance of early identification of possible risk factors and filicidal tendencies
Keywords: Filicide; Mental disturbance; Spousal revenge; Awareness